2018
DOI: 10.1016/j.yhbeh.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental chronic traffic noise exposure on adult and nestling corticosterone levels, and nestling body condition in a free-living bird

Abstract: Transportation noise affects urbanized, rural, and otherwise unaltered habitats. Given expanding transportation networks, alterations in the acoustic landscapes experienced by animals are likely to be pervasive and persistent (i.e. chronic). It is important to understand if chronic noise exposure alters behavior and physiology in free-living animals, as it may result in long-lasting impacts, such as reduced reproductive success. Here, we experimentally tested the effects of chronic traffic noise on baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…In our study system, Peromyscus mice are known to remove seeds at higher rates on noisy sites [13], which may also discourage scrub jays from caching seeds near noisy wellpads. Additionally, episodic memory of the inability to communicate with conspecifics [1,43,44], inability to eavesdrop and prey upon nests of other species [6], or altered glucocorticoid levels [19,45] due to elevated perceived risk that is associated with hampered acoustic surveillance for threats [46][47][48][49] could increase the long-term avoidance of noise. Understanding to what degree episodic-like memory may contribute to patterns of habitat use and ecological interactions is an intriguing avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In our study system, Peromyscus mice are known to remove seeds at higher rates on noisy sites [13], which may also discourage scrub jays from caching seeds near noisy wellpads. Additionally, episodic memory of the inability to communicate with conspecifics [1,43,44], inability to eavesdrop and prey upon nests of other species [6], or altered glucocorticoid levels [19,45] due to elevated perceived risk that is associated with hampered acoustic surveillance for threats [46][47][48][49] could increase the long-term avoidance of noise. Understanding to what degree episodic-like memory may contribute to patterns of habitat use and ecological interactions is an intriguing avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced breeding performance near roads could also arise if these territories are of lower quality because of chemical pollution, the presence and movement of cars and different vegetation (Reijnen et al, 1996;Summers et al, 2011;Jack et al, 2015), and/or if these territories are more likely to be occupied by lower quality individuals (e.g. first time breeders) unable to secure better quality territories further away from roads (Injaian et al, 2018c). Moreover, noise does not always reduce bird abundance: Francis et al (2009) investigated noise impact on community composition at gas well exploitation sites and found that noisy sites had fewer predator species than quiet sites, but that the total number of birds did not differ between sites.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding noise pollution specifically, results are also contrasting. Studies using nestling birds (incapable of avoiding noise sources) as focal individuals have found that experimental exposure to traffic noise can lead to both increases and decreases of baseline CORT levels (Injaian et al 2018b(Injaian et al , 2019Crino et al 2013;Flores et al 2019) and no effects at all (MeillĂšre et al 2015a, b;Angelier et al 2016). Most correlational studies reported no influence of noise exposure on CORT (Crino et al 2011;Casasole et al 2017).…”
Section: Introductionmentioning
confidence: 99%